1998
DOI: 10.1159/000010006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Creatinine Kinase in the Diagnosis of Ectopic Pregnancy

Abstract: The role of creatinine kinase (CK) in the diagnosis of ectopic pregnancy was studied. We selected 56 patients divided into 4 groups. Group A consisted of 10 patients with asymptomatic tubal pregnancy, group B consisted of 11 patients with symptomatic tubal pregnancy whereas groups C and D consisted of 20 and 15 patients with normal and threatened intrauterine pregnancy, respectively. Serum samples of CK were taken from all patients on admission. No significant difference was observed in the median CK value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…The cut‐off of total CK to predict tubal rupture was 147 IU/L, which is close to our previous report . Most of the previous studies which have reported conflicting interest in this frame were carried on small sample groups . Gnisci et al .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The cut‐off of total CK to predict tubal rupture was 147 IU/L, which is close to our previous report . Most of the previous studies which have reported conflicting interest in this frame were carried on small sample groups . Gnisci et al .…”
Section: Discussionsupporting
confidence: 87%
“…7 Most of the previous studies which have reported conflicting interest in this frame were carried on small sample groups. [8][9][10] Gnisci et al elucidated the significance of total CK in the management of EP and reported that the CK levels were found to predict the success of methotrexate injection in EP cases. 3 Limited data is available on the isoforms of CK in EP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not find any difference in creatine kinase levels between ruptured isthmic and ampullary ectopic pregnancy in the women with symptoms of peritoneal irritation, which could provide a clue as to the extent of tubal damage and associated intraperitoneal bleeding. Furthermore, no difference could be demonstrated in creatine kinase levels between symptomatic and asymptomatic patients, which agrees with previous reports 2,3,12 .…”
Section: Discussionsupporting
confidence: 93%